2016
DOI: 10.1039/c6nj00478d
|View full text |Cite
|
Sign up to set email alerts
|

A new NBS/oxone promoted one pot cascade synthesis of 2-aminobenzimidazoles/2-aminobenzoxazoles: a facile approach

Abstract: A rapid and transition metal free synthesis of 2-aminobenzazoles using readily available substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This green oxidant is a mixture of three inorganic salts (2KHSO 5 •KHSO 4 •K 2 SO 4 ), with potassium peroxymonosulfate (KHSO 5 ) being the active species. The synthesis of important heterocyclic compounds was accomplished using Oxone ® , such as chromene and carbazoles (Reddy, Kannaboina & Das, 2017), benzimidazoles (Daswani et al, 2016), benzoxazoles (Hati et al, 2016), pyrazole (Kashiwa et al, 2016) and pyridine derivatives (Swamy et al, 2016). Furthermore, it was used in intramolecular cycloaddition (More & Ramana, 2016) and cyclization reactions (Sharma et al, 2016), in the synthesis of α-bromoketones (Rammurthy et al, 2017), in halogenation reactions of quinolines (Wang et al, 2016), oxidation of alcohols to carbonyl compounds (Mishra & Moorthy, 2017) and in the synthesis of iodohydrins and iodoarenes (Soldatova et al, 2016).…”
Section: Five Main Synthetic Routes Have Been Developed To Construct mentioning
confidence: 99%
“…This green oxidant is a mixture of three inorganic salts (2KHSO 5 •KHSO 4 •K 2 SO 4 ), with potassium peroxymonosulfate (KHSO 5 ) being the active species. The synthesis of important heterocyclic compounds was accomplished using Oxone ® , such as chromene and carbazoles (Reddy, Kannaboina & Das, 2017), benzimidazoles (Daswani et al, 2016), benzoxazoles (Hati et al, 2016), pyrazole (Kashiwa et al, 2016) and pyridine derivatives (Swamy et al, 2016). Furthermore, it was used in intramolecular cycloaddition (More & Ramana, 2016) and cyclization reactions (Sharma et al, 2016), in the synthesis of α-bromoketones (Rammurthy et al, 2017), in halogenation reactions of quinolines (Wang et al, 2016), oxidation of alcohols to carbonyl compounds (Mishra & Moorthy, 2017) and in the synthesis of iodohydrins and iodoarenes (Soldatova et al, 2016).…”
Section: Five Main Synthetic Routes Have Been Developed To Construct mentioning
confidence: 99%
“…reported their synthesis via intramolecular C−N bond formation between an aryl halide and guanidine moiety using either Cu or Pd catalysis . Besides, their preparation could also be accomplished by Cu‐catalyzed amination of 1,2‐dihaloarenes with guanidines, Cu‐catalyzed cascade addition and cyclization of o ‐haloanilines and carbodiimides, Co‐catalyzed oxidative isocyanide insertion to diamines, treatment of quinones with guanidine derivatives, Cu‐catalyzed electrophilic amination of 1‐methylbenzimidazole by C−H zincation or alumination, Cu‐catalyzed three‐component reactions using cyanamides, arylboronic acids and amines, and an NBS/oxone promoted one‐pot cascade synthesis . Recently, the Phakhodee and Chang groups synthesized multifunctional 2‐aminobenzimidazoles from N ‐substituted o ‐diaminoarenes and isothiocyanates.…”
Section: Introductionmentioning
confidence: 99%
“…43 Recently, the Oxone ® has been used in the preparation of important heterocycles, for example in the synthesis of pyrazoles, 44 benzoxazoles and benzimidazoles. 45,46 Other examples are included, such as synthesis of isoxazolines and isoxazoles, 47 chromene and carbazole, 48 and pyridines and pyrimidines derivatives. 49 Our research group recently reported the use of Oxone ® to generate electrophilic species of selenium evidencing its application in selenylation reactions.…”
Section: Introductionmentioning
confidence: 99%